Pre-treatment loss to follow-up in adults with pulmonary tuberculosis in Kenya - contributing factors and evidence-based interventions - Mulaku, Mercy Namuma (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.